Blizzard Rescue: A Branches Book - Rajan, Rekha S.; Lovett, Courtney (New York : Branches/Scholastic, 2024)
The Jackson family rush to Minnesota where a blizzard is putting both people and animals in danger from freezing temperatures, and blinding snow.
new kids book 2024 winter.
Ages 6-8.
Grades 2-3.
Keywords: Blizzards -- Juvenile fiction; Animal rescue -- Juvenile fiction; Natural disasters -- Juvenile fiction; Families -- Juvenile fiction; Animal rescue -- Fiction; Natural disasters -- Fiction; Family life -- Fiction; JUVENILE FICTION / Readers / Chapter Books; JUVENILE FICTION / Action & Adventure / General; Blizzards -- Fiction; Minnesota -- Juvenile fiction; Minnesota -- Fiction